Borders to Bridges: Awakening Critical Consciousness - Ditchfield, Lynn Glixon (Radical Teacher, 2021)
Concerned educators seek ways to counter the myths, mistrust, false rumors, ignorance and fears surrounding issues of immigration, migration, race and ethnicity that have so negatively affected our students, schools and communities. This article presents an approach through a sample lesson plan, framework and synopsis of content and theoretical underpinnings of the chapters of Borders to Bridges: Creativity-Based Immigration Curriculum Guidebook. The guidebook and successful pilot program challenge the standardized “teach-to-the-test” narrative by proposing a student-directed curriculum which utilizes creativity to awaken critical consciousness.